2018
DOI: 10.1111/nmo.13319
|View full text |Cite
|
Sign up to set email alerts
|

Rikkunshito simultaneously improves dyspepsia correlated with anxiety in patients with functional dyspepsia: A randomized clinical trial (the DREAM study)

Abstract: Rikkunshito may be beneficial for FD patients to simultaneously treat gastrointestinal and psychological symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 36 publications
5
64
0
3
Order By: Relevance
“…These results are in line with a previous study by Tominaga et al, 25 showing beneficial effects of rikkunshito on PDS symptoms. These results are in line with a previous study by Tominaga et al, 25 showing beneficial effects of rikkunshito on PDS symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in line with a previous study by Tominaga et al, 25 showing beneficial effects of rikkunshito on PDS symptoms. These results are in line with a previous study by Tominaga et al, 25 showing beneficial effects of rikkunshito on PDS symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, these symptoms, scored on the LPDS diary, were only improved after rikkunshito treatment compared with the run-in phase of the study. These results are in line with a previous study by Tominaga et al, 25 showing beneficial effects of rikkunshito on PDS symptoms. However, for several symptoms assessed with other questionnaires in the current study, significant improvements from run-in were found for both rikkunshito and placebo, or for placebo alone.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The studies published between 1991 and 2019 were included. Patients had FD, [15][16][17][18][19][20][21][22]13,14,[23][24][25][26][27][28][29][30][31][32] and constipation [56][57][58][59][60][61][62] in 19, 23 and 7 trials respectively. More than 33 different kinds of herbal formulae were tested in the included trials.…”
Section: Resultsmentioning
confidence: 99%
“…26,50 On the other hand, there are limited reports on the use of the modified FSSG in placebo-controlled double-blind controlled trials in patients with FD, 51 and further verification is necessary. In addition, many doctors use the revised FSSG to diagnose FD and evaluate the effects of FD treatment in daily medical care.…”
Section: Modified Fssg Scores After Treatment Amentioning
confidence: 99%